Identification of Candida colliculosa in an oral ulcer of a pediatric hematological patient - Ballardin, Bárbara Soldatelli; Mobile, Rafael Zancan; Leal, Gustavo André; Torres-Pereira, Cassius Carvalho; Schussel, Juliana Lucena (Journal of Oral Diagnosis, 2022)
Introduction: Candida colliculosa is a yeast of food origin classified as Non-Albicans Candida (NAC), with its pathogenic potential confirmed, but little known. Like other opportunistic infections, diseases caused by NAC species are most commonly found in immunosuppressed patients. Objectives: The objective of this work is to report the case of a pediatric patient who developed an atypical lesion associated with Candida collicu- losa in the mouth. Case report: A 9-year-old boy under chemotherapeutic treatment for Acute Myeloid Leukemia developed edema in the lower lip, with a persistent crusted ulcer circumscribed by an erythematous, painless, and progressing negatively. He was using antibiotics, antifungals, antiemetics, and antihistamines. Results: It was decided to perform complementary exams for final diagnosis. Cell smears were collected for exfolia- tive cytology, direct mycological, bacterial and viral culture, and fungi investigation. No viruses and bacteria were identified. A direct mycological examination showed yeast cells without pseudohyphae and a Maldi-TOF technique confirmed the diagnosis of Candida colliculosa. Final considerations: The use of antifungal agents associated with the patient’s immunological recovery led to the complete healing of the lesion and hospital discharge. Identification of the fungal species was important not only to establish the diagnosis and most appropriate treatment but also to avoid the fungus spreading in the hospital environment.